Analisis Tindakan Main Hakim Sendiri Menurut Hadits Riwayat Muslim No 2577 Dan Pasal 170 KUHP - Faliani Zaliaokta; Tajul Arifin (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
Vigilantism (eigenrichting) occurs because a person or group tries to carry out an act of judgment against someone that is considered guilty without seeing or going through the legal process first. According to criminal law, sanctions for perpetrators of vigilante crimes that result in death are regulated in Article 170 of the Criminal Code with a maximum penalty of 12 years in prison. Meanwhile, in Islamvigilantism is also a despicable thing because Muslims are taught to do tabayyun (seek clarity) first before acting. The act of taking the law into your own hands by committing persecution is an act that is not in accordance with Islamic teachings because persecution is included in unjust actions. Allah Swt said in Hadith No. 2577 from Muslim that acts of injustice, especially against fellow Muslims, are prohibited. The analysis conducted in this journal found that vigilantism is not only prohibited by the state but also by religion. unfortunately, not much attention is given by the community regarding vigilante cases that often occur in Indonesia. Therefore, the main purpose of compiling this journal is none other than as a window to open the minds of the general public who often underestimate vigilantism in Indonesia.